2020
DOI: 10.3389/fcell.2020.00508
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis Reveals a Mitochondrial Remodeling of βTC3 Cells in Response to Nanotopography

Abstract: Recently, using cluster-assembled zirconia substrates with tailored roughness produced by supersonic cluster beam deposition, we demonstrated that β cells can sense nanoscale features of the substrate and can translate these stimuli into a mechanotransductive pathway capable of preserveing β-cell differentiation and function in vitro in long-term cultures of human islets. Using the same proteomic approach, we now focused on the mitochondrial fraction of βTC3 cells grown on the same zirconia substrates and char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…A high number of identified proteins (270 out of 397; 68) were classified as known or predicted to be mitochondrial proteins. The mitochondrial enrichment procedure applied to increase mitochondrial protein abundance exhibited an efficiency comparable to that observed in other studies (Alberio et al, 2017;Maffioli et al, 2020). The presence of non-mitochondrial proteins (i.e., endoplasmic reticulum, cytoskeletal proteins) is due to the physical connection between the mitochondria and other subcellular organelles (Dolman et al, 2005;Rowland and Voeltz, 2012;Xia et al, 2019;Giacomello et al, 2020) as already demonstrated in previous studies (Rezaul et al, 2005;Alberio et al, 2017;Chae et al, 2018).…”
Section: Shotgun Proteomics Analysis Reveals Changes In Mitochondrialsupporting
confidence: 77%
“…A high number of identified proteins (270 out of 397; 68) were classified as known or predicted to be mitochondrial proteins. The mitochondrial enrichment procedure applied to increase mitochondrial protein abundance exhibited an efficiency comparable to that observed in other studies (Alberio et al, 2017;Maffioli et al, 2020). The presence of non-mitochondrial proteins (i.e., endoplasmic reticulum, cytoskeletal proteins) is due to the physical connection between the mitochondria and other subcellular organelles (Dolman et al, 2005;Rowland and Voeltz, 2012;Xia et al, 2019;Giacomello et al, 2020) as already demonstrated in previous studies (Rezaul et al, 2005;Alberio et al, 2017;Chae et al, 2018).…”
Section: Shotgun Proteomics Analysis Reveals Changes In Mitochondrialsupporting
confidence: 77%
“…We found that the extracellular matrix nanotopography, via a mechanotransduction pathway which involves mechanosensitive integrins, reorganisation of the actin cytoskeleton and changes in the nuclear architecture, triggers a specific transcriptional program necessary for the metabolic adaptation of cells to the new environment. This response is mediated by modifications of the mitochondrial activity and dynamics and involves the crosstalk of mitochondria with other organelles as lysosomes and ER, where iron exchange takes place [ 72 , 74 , 79 , 112 ], also envisioning a possible role of iron in this signalling.…”
Section: Iron Is Required For the Normal Beta-cell Functionmentioning
confidence: 99%
“…The supernatant containing peptides and low-molecular-weight proteins were collected, dried (Speed Vacuum), dissolved in 1% (v/v) formic acid, and desalted (Zip-Tip C18, Millipore) before mass spectrometric (MS) analysis. MS/MS analysis was carried out by a Orbitrap Fusion Tribrid mass spectrometer (Thermo Fisher Sci., Waltham, MA, USA), as previously described [ 39 ]. Data Base search was performed using the Sequest search engine of Proteome Discoverer 1.4 (Thermo Fisher Sci.)…”
Section: Methodsmentioning
confidence: 99%